Good-Practice Note : Governance and Anti-Corruption Innovations in the Malawi Social Action Fund Project - Aklilu, Petros; Agarwal, Sanjay (World Bank, Washington, DC, 2012)
The World Bank supported three phases Malawi Social Action Fund (MASAF) project was first approved in 1996. Malawi, with a population of 13 million, is a low income country with one of the lowest per capita incomes in Sub-Saharan Africa. Malawi continues to face a variety of social, economic, political and administrative challenges including high inflation, low salaries/pensions of public officials, chronic resource shortages, dearth of public goods and services, unethical individual behavior, and kinship and nepotism. As a result of these factors, corruption remains a major problem in Malawi. In response to these challenges, Malawi has introduced a number of initiatives aimed at promoting good governance and fighting endemic corruption. In May 2004, President Bingu Wa Mutharika, immediately after taking office adopted a zero tolerance stance on corruption. This was subsequently formalized into a declaration on zero tolerance on corruption in February 2007. MASAF projects' commendable work in identifying governance and accountability risks and integrating mitigation measures into proposed project activities.